2022
DOI: 10.3390/biology11081225
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Tamoxifen on Tolerogenic Cells in Cancer

Abstract: Tamoxifen (TAM) is the most prescribed selective estrogen receptor modulator (SERM) to treat hormone-receptor-positive breast cancer patients and has been used for more than 20 years. Its role as a hormone therapy is well established; however, the potential role in modulating tolerogenic cells needs to be better clarified. Infiltrating tumor-microenvironment-regulatory T cells (TME-Tregs) are important as they serve a suppressive function through the transcription factor Forkhead box P3 (Foxp3). Abundant studi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 127 publications
0
1
0
Order By: Relevance
“…Another type of combination has been proposed in a phase II clinical study against hormone-resistant breast cancer (BC) [ 113 ], which is a type of BC that does not respond to treatment with hormones such as tamoxifen. The latter is a drug used to treat and prevent BC by inhibiting the effects of estrogen on breast tissue, which can slow or inhibit the growth of breast tumor cells that depend on estrogen to develop [ 132 ]. In fact, 43 patients with metastatic BC who had progressed on hormone therapy were recruited for this trial.…”
Section: Anticancer Clinical Investigations Of Vorinostatmentioning
confidence: 99%
“…Another type of combination has been proposed in a phase II clinical study against hormone-resistant breast cancer (BC) [ 113 ], which is a type of BC that does not respond to treatment with hormones such as tamoxifen. The latter is a drug used to treat and prevent BC by inhibiting the effects of estrogen on breast tissue, which can slow or inhibit the growth of breast tumor cells that depend on estrogen to develop [ 132 ]. In fact, 43 patients with metastatic BC who had progressed on hormone therapy were recruited for this trial.…”
Section: Anticancer Clinical Investigations Of Vorinostatmentioning
confidence: 99%
“…Tamoxifen (TAM) is the most prescribed selective estrogen receptor modulator (SERM) for hormone receptor positive breast cancer patients. 154 A recent study found that the protein expression level of ATF3 in tamoxifen resistant (TamR) MCF-7 cells was significantly higher than that in corresponding parent cancer cells. Further research found that m 6 A-modified ATF3 could regulate the resistance of breast cancer cells to tamoxifen.…”
Section: Rna Modifications Regulate Tumor Treatment Resistancementioning
confidence: 99%